The core normal Type Ia supernova 2019np – an overall spherical explosion with an aspherical surface layer and an aspherical 56Ni core. Issue 1 (16th January 2023) - Hoeflich, Peter; Yang, Yi; Baade, Dietrich; Cikota, Aleksandar; Maund, Justyn R; Mishra, Divya; Patat, Ferdinando; Patra, Kishore C; Wang, Lifan; Wheeler, J Craig; Filippenko, Alexei V; Gal-Yam, Avishay; et al.
ABSTRACT: Optical spectropolarimetry of the normal thermonuclear supernova (SN) 2019np from −14.5 to +14.5 d relative to B -band maximum detected an intrinsic continuum polarization ( p cont ) of 0.21 ± 0.09 per cent at the first epoch. Between days −11.5 and +0.5, p cont remained ∼0 and by day +14.5 was again significant at 0.19 ± 0.10 per cent. Not considering the first epoch, the dominant axis of Si II λ6355 was roughly constant staying close the continuum until both rotated in opposite directions on day +14.5. Detailed radiation-hydrodynamical simulations produce a very steep density slope in the outermost ejecta so that the low first-epoch p cont ≈ 0.2 per cent nevertheless suggests a separate structure with an axis ratio ∼2 in the outer carbon-rich (3.5–4) × 10 −3 M⊙ . Large-amplitude fluctuations in the polarization profiles and a flocculent appearance of the polar diagram for the Ca II near-infrared triplet (NIR3) may be related by a common origin. The temporal evolution of the polarization spectra agrees with an off-centre delayed detonation. The late-time increase in polarization and the possible change in position angle are also consistent with an aspherical 56 Ni core. The p cont and the absorptions due to Si II λ6355 and Ca II NIR3 form in the same region of the extended photosphere, with an interplay between line occultation and thermalization producing p . Small-scale polarization features may be due to small-scale structures, but many could be related to atomic patterns of the quasi-continuum; they hardly have an equivalent in the total-flux spectra. We compare SN 2019np to other SNe and develop future objectives and strategies for SN Ia spectropolarimetry.